Jizō-kō and Sentai-Jizō wo horu kai: Finding new bonds through Jizō carving activity - Aliise Eisho Donnere (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2023)
This article investigates how Buddhist temples in modern Japan use the image of bodhisattva Jizō to attract more people to their precincts and to make closer ties with their parishioners through events known as Kō (regular temple events, usually concentrating on worshipping a bodhisattva, in this case - bodhisattva Jizō). The article presents an insight into three traditional Kō and one original event that grew out of a traditional Kō in the largest city of Tohoku region - Sendai. The author will attempt to show that the format of traditional Jizō-kō is quite flexible and allows the head priest to interact with the members in a relaxed and intimate atmosphere. Finally, we will have a look at a slightly changed format of Jizō-kō - Jizō statues carving event in Kōzenji, where the participants hardly engage in rituals, but instead spend some quality time carving small wooden statues and talking about Buddhism and the ideal way of life. The author argues that this kind of adaptation of a traditional event to the needs of modern people doesn’t make it less “Buddhist”, but instead allows the participants to get a deeper understanding of what they are practicing.